Understanding the nature of dropouts in MFIs: Evidence from rural Bangladesh - Ashraf, Mohammad A.; Ibrahim, Yusnidah (IISTE, 2014)
The present study aims to comprehend the nature of drop out from the microfinance institutes (MFIs) in Bangladesh.To this aim, the research incorporates several variables ranging from the demographic to demandled factors that may affect the dropping out behavior of the rural poor in MFIs.Multiple regression model has been used to analyze the data (n = 280) that are collected from the dropout-members from six regions of Bangladesh.The findings demonstrate that eleven of fourteen explanatory variables including the demographics are statistically significant to influence the dropping out behavior of the dropouts in rural Bangladesh.